The luminescent Chalcones. Its potential use as a luminescent and antitumoral agents - Ramirez, Rodrigo; Echeverria, Cesar; Alvarado-Soto, Leonor; Escobar, Carlos A. (Vitae, 2022)
BACKGROUND: Hepatocellular carcinoma (HCC) is one of the most diagnosed cancers worldwide. Chemoprevention of HCC can be achieved using natural or synthetic compounds that reverse, suppress, detect, or prevent cancer progression. OBJECTIVES: In this study, both the antiproliferative effects and luminescent properties of 2’-hydroxychalcones were evaluated. METHODS: Cell viability was evaluated using the 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) colorimetric assay, spectroscopy assays, and density functional theory (DFT) calculations were used to determine the luminescent properties of 2´-hydroxychalcones. RESULTS: Cytotoxic effects of 2´-hydroxychalcones were observed over the HepG2 and EA.hy926 cells. Since the chalcone moiety could be used as a fluorescent probe, these compounds may be helpful in cancer diagnosis and tumor localization. They may enable tumor observation and regression through the fluorescence during treatment; therefore, the compounds are a potential candidate as novel anticancer agents acting on human hepatomas. CONCLUSIONS: This report describes the chalcones’ use as a specific luminescent biomarker in tumor cells. We also report the cellular uptake of 2’-hydroxychalcones, their cellular distribution, and the mechanisms that may be responsible for their cytotoxic effects.